Isolation and partial characterisation of galactosespecific lectins from African yam beans, Sphenostylis stenocarpa Harms - Machuka, J.S.; Okeola, O.G.; Els, J.V.D.; Chrispeels, M.J.; Leuven, F. van; Peumans, W.J. (1999)
A new galactose-specific lectin was isolated from African yam bean (Sphenostyles stenocarpa Harms) by affinity chromatography on galactose-Sepharose 4B. SDS–PAGE analysis resulted in four polypeptide bands of approximately 27, 29, 32 and 34 kDa, respectively. Based on the analysis of carbohydrate content and native PAGE, it is likely that the Sphenostyles lectin is a tetrameric glycoprotein with Mr of approximately 122 kDa. N-terminal protein sequencing of purified lectins from four different Sphenostyles accessions shows that the four polypeptides have largely identical amino acid sequences. The sequences contain the conserved consensus sequence F-F–LILG characteristic of legume lectins, as well as Phaseolus vulgaris proteins in the arcelin-α-amylase inhibitor gene family. The lectin agglutinates both rabbit and human erythrocytes, but with a preference for blood types A and O. Using Western blotting, the lectin was shown to accumulate rapidly during seed development, but levels dropped slightly as seeds attained maturity. This is the first time a lectin has been purified from the genus Sphenostyles. The new lectin was assigned the abbreviation LECp.SphSte.se.Hga1.